Patent Trend in Research Centers at Cibinong Science and Technology Park Surrounding for Determining Technology Focus - Yaniar, Harini; Wicaksono, Adityo (The Asian Journal of Technology Management (AJTM), 2017)
Abstract. Focusing in a specific technology sector would be a great strategy for early developed Science and Technology Park (STP) especially in Indonesia. Each STP has its own concept considering the resources and technology supply. This should be main considerations in determining STP focus. Cibinong Science and Technology Park (CSTP) is surrounded by 4 research centers, and Center for Innovation. Their patent database within 5 years has been studied to determine CSTP focus. By using qualitative method and descriptive analysis, the results showed that the top priority is agriculture, followed by pharmaceutical. Moreover, the strategic areas for development in agriculture sector include: soil working; horticulture; preservation of bodies; and biocides. And in pharmaceutical sub sector includes: preparations for medical, dental, or toilet purposes; specific therapeutic activity of chemical compounds or medicinal preparations; and heterocyclic compounds. Furthermore, China can be a benchmark for technology development in agriculture, while US for technology development in pharmaceutical.Keywords:Â  Technology focus, patent trend, CSTP surrounding, research center, STP